Efficacy and safety of PARP inhibitors in the treatment of advanced ovarian cancer: An updated systematic review and meta-analysis of randomized controlled trials. (January 2021) - Hao, Jiatao; Liu, Ying; Zhang, Taohong; He, Jinmei; Zhao, Haoyi; An, Ruifang; Xue, Yan
Highlights: PARP inhibitors showed more survival benefits than control therapy, irrespective of BRCA status. Performance of the PARP inhibitors declines slightly due to increased risks of selected adverse events. Most of the treatment-related toxicities occurred during the early stage. Most toxicities were managed by dose interruption or dose reduction, rather than dose discontinuation. Abstract: Background: Poly-ADP-ribose polymerase (PARP) inhibitors have emerged as a novel class of therapeutics for ovarian cancer (OC); however, PARP inhibitors present a class effect adverse-event profile. Methods: A comprehensive literature review was performed for phase II or III randomized controlled trials (RCTs) published up to and including January 2020. We analyzed relevant clinical trials reporting the efficacy and toxicity profile of PARP inhibitors in patients with advanced OC. We estimated hazard ratios (HRs), incidences, risk ratios (RRs) and relative 95 % confidence intervals (95 % CI) for progression-free survival (PFS) and selected adverse events, using Stata 12.0 software package. Results: The systematic review process yielded 10 eligible trials comprising 4, 241 patients with advanced OC for survival analysis and 4553 patients for evaluation of toxicity profile. The pooled HR (PARP inhibitor vs control group) for PFS was 0.41 (95 % CI, 0.35−0.50) in overall patients, 0.51 (95 % CI, 0.40−0.64) in unselected setting, 0.32 (95 % CI, 0.26−0.39) in BRCA mutation setting, and 0.57 (95 % CI, 0.41−0.78) in wild-type setting. Patients treated with PARP inhibitors exhibited higher risks of all-grade and high-grade haematological toxicities, including anemia, leucopenia, neutropenia, thrombocytopenia ( P < 0.05), and also presented higher risks of all-grade gastrointestinal side effects, including constipation, diarrhea, nausea, and vomiting as well as high-grade nausea and vomiting ( P < 0.05). Conclusions: This study indicated that the use of PARP inhibitor provided substantial progression-free survival (PFS) benefits, irrespective of BRCA mutation status; however, treatment with PARP inhibitor was associated with increased risks of selected treatment-related adverse events.